Imagining the Self in South Asian and African Literatures - Sidhu, Inder (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2023)
This book examines the idea of the self in Anglophone literatures from British colonies in Africa and the subcontinent, and in the context of intercultural encounter, literary hybridity and globalization. The project examines texts by eight authors across the colonial, postwar and post-9/11 eras - Olaudah Equiano, Sake Dean Mahomet, Henry Callaway, R.C. Temple, Amos Tutuola, G.V. Desani, Tsitsi Dangarembga and Aravind Adiga - in order to map different strategies of selfhood across four fields of literature: autobiographical life writing, folk anthology, postwar fabulism, and contemporary realism. Drawing on historical analysis, psychological inquiry, comparative linguistics, postcolonial criticism and social theory, this book responds to a renewed emphasis on the narrative strategies and creative choices involved in a literary construction of the self. Threaded through this investigation is an analysis of the effects of globalization, or the intensification of intercultural and dialogic complexity over time. Inder Sidhu holds a PhD in English literature from King's College London, UK. He works with graduate students at the Ontario College of Art & Design University's Writing and Learning Centre and teaches at the University of Guelph-Humber and Humber College in Toronto, Canada.
1 -- Introduction -- 2 Negotiating Difference: Positioning the Self in Sake Dean Mahomet's The Travels of Dean Mahomet, a Native of Patna in Bengal, Through Several Parts of India, While in the Service of the Honourable the East India Company (1794) and Olaudah Equiano's The Interesting Narrative of the Life of Olaudah Equiano, or Gustavus Vassa, The African (1789) -- 3 Importing Knowledge and Theory: The Authorial Self and the Expert Position in Henry Callaway's Nursery Tales, Traditions, and Histories of the Zulu (1868) and R. C. Temple's Legends of the Punjab (1884-1900). - 4 The Divisible Self - Global-Local Journeys in G.V. Desani's All About H. Hatterr (1948) and Amos Tutuola's The Palm-Wine Drinkard (1952) -- 5 Talking Back - The Uncertain Self and Counter-Narratives in Aravind Adiga's The White Tiger (2008) and Tsitsi Dangarembga's The Book of Not (2006) -- 6 Conclusion -- 8 Bibliography.
Keywords: African literature; Oriental literature; Literature, Modern -- 19th century; African Literature; Asian Literature; Nineteenth-Century Literature